2003
DOI: 10.1038/sj.bjc.6600975
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyles, environmental and phenotypic factors associated with lip cancer: a case–control study in southern Spain

Abstract: The aim of this study was to identify factors related to lip cancer (LC) considering individual characteristics and sociodemographic factors. A case -control study was carried out in the province of Granada (Andalusia, southern Spain). The cases were 105 males with squamous-cell carcinoma of the lip, diagnosed between 1987 and 1989 (aged 20 -70 years) and identified by means of a populationbased Cancer Registry. As controls, a randomised populational sample of 239 males, stratified by age, was used. Multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
17

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 27 publications
(23 reference statements)
1
73
0
17
Order By: Relevance
“…O contato dos produtos presentes no cigarro ou cachimbo na região labial podem consistir em fator que possibilitem maior risco de lesões malignas. 14,19,20 Vale destacar que o hábito tabagista é considerado um problema de saúde pública, visto que segundo a Organização Mundial de Saúde (OMS) estima que de 2000 a 2030 o número de mortes anuais atribuíveis ao tabagismo aumentará de 4,9 para 10 milhões. 21 Ainda na observação dos hábitos, deve-se apontar os resultados referentes ao etilismo posto que pode haver uma interação entre o consumo de álcool e o hábito de repousar o cigarro na boca.…”
Section: Resultados Resultados Resultados Resultados Resultadosunclassified
See 1 more Smart Citation
“…O contato dos produtos presentes no cigarro ou cachimbo na região labial podem consistir em fator que possibilitem maior risco de lesões malignas. 14,19,20 Vale destacar que o hábito tabagista é considerado um problema de saúde pública, visto que segundo a Organização Mundial de Saúde (OMS) estima que de 2000 a 2030 o número de mortes anuais atribuíveis ao tabagismo aumentará de 4,9 para 10 milhões. 21 Ainda na observação dos hábitos, deve-se apontar os resultados referentes ao etilismo posto que pode haver uma interação entre o consumo de álcool e o hábito de repousar o cigarro na boca.…”
Section: Resultados Resultados Resultados Resultados Resultadosunclassified
“…21 Ainda na observação dos hábitos, deve-se apontar os resultados referentes ao etilismo posto que pode haver uma interação entre o consumo de álcool e o hábito de repousar o cigarro na boca. 19 Os achados referentes a esse hábito foram inferiores ao do tabagismo, no entanto, há um viés de informação na medida em que envolve certo constrangimento por parte dos pacientes em relatar o hábito etilista.…”
Section: Resultados Resultados Resultados Resultados Resultadosunclassified
“…The dose-response relationship with recalled average annual hours spent in outdoor activities was inconsistent: with < 30 hours as the reference category, the odds ratios were 2.6 (95%CI: 1.0-6.5) for 30-99 hours; 1.8 (95%CI: 0.7-4.6) for 100-299 hours; and, 4.7 (95%CI: 1.9-12.1) for > 300 hours. The second, which included men only (Perea-Milla López et al, 2003), found no evidence of an increased risk for cancer of the lip with estimates of cumulative sun exposure during leisure time or holiday. Risk was increased with cumulative sun exposure in outdoor work during the summer months, but without any dose-response (OR,; with wide confidence intervals).…”
Section: Cancer Of the Lipmentioning
confidence: 99%
“…[2,3] Histopatolojik olarak en sık yassı hücreli karsinom (YHK)'lar (%90) görülmekle beraber bazal hücreli karsinomlar ve tükürük bezi kanserlerine de rastlanabilir. [3][4][5] Dudak kanserleri özellikle 6. ve 7. dekadda, beyaz ırkta ve erkeklerde sıktır. [4] Bu kanserler sıklıkla radyodermitis, kronik kelitis ve kseroderma pigmentozum gibi pre-kanseröz lezyonların zemininde gelişebilmektedir.…”
unclassified